The Human-Specific STING Agonist G10 Activates Type I Interferon and the NLRP3 Inflammasome in Porcine Cells - Ming, Sheng-Li; Zeng, Lei; Guo, Yu-Kun; Zhang, Shuang; Li, Guo-Li; Ma, Ying-Xian; Zhai, Yun-Yun; Chang, Wen-Ru; Yang, Le; Wang, Jiang; Yang, Guo-Yu; Chu, Bei-Bei (Frontiers in Immunology, 2020)
Pigs have anatomical and physiological characteristics comparable to those in humans, and therefore, are a favorable model for immune function research. Interferons (IFNs) and inflammasomes have essential roles in the innate immune system. Here, we report that G10, a human specific agonist of stimulator of interferon genes (STING), activates both type I IFN and the canonical NLRP3 inflammasome in a STING-dependent manner in porcine cells. Without a priming signal, G10 alone transcriptionally stimulated Sp1-dependent p65 expression, thus, triggering activation of the NF-κB signaling pathway and thereby priming inflammasome activation. G10 was also found to induce potassium efflux- and NLRP3/ASC/Caspase-1-dependent secretion of IL-1β and IL-18. Pharmacological and genetic inhibition of NLRP3 inflammasomes increased G10-induced type I IFN expression, thereby preventing virus infection, suggesting negative regulation of the NLRP3 inflammasome in the IFN response in the context of STING-mediated innate immune activation. Overall, our findings reveal a new mechanism through which G10 activates the NLRP3 inflammasome in porcine cells and provide new insights into STING-mediated innate immunity in pigs compared with humans.